The combination of organic and inorganic fertilizers influence the weed growth, productivity and soil fertility of monsoon rice - Ghosh, Dibakar; Brahmachari, Koushik; Skalický, Milan; Roy, Dibakar; Das, Anupam; Sarkar, Sukamal; Moulick, Debojyoti; Brestič, Marián; Hejnak, Vaclav; Vachova, Pavla; Hassan, Mohamed M.; Hossain, Akbar (PloS one, 2022)
Synthetic fertilizer and herbicides encompass the largest share in nutrient and weed management on food grain crops that create serious environmental issues. Integrated nutrient and non-chemical weed management approaches may help to reduce the chemical load in the environment, maintaining higher weed control efficiency and yield. A field experiment was conducted for two consecutive monsoon seasons during 2015 and 2016 in farm fields to develop a profitable and sustainable rice production system through integrated nutrient and weed management practices. A varied combination of nutrients either alone or integrated with chemical and non-chemical weed management were tested on transplanted rice in a factorial randomized block design with three replications. The results showed that the integration of concentrated organic manures with chemical fertilizer effectively inhibited weed growth and nutrient removal. Integration of nutrient and weed management practices significantly enhanced 9% biomass growth, 10% yield of the rice crop along with 3–7% higher nutrient uptake. Brassicaceous seed meal (BSM) and neem cake also had some influence on weed suppression and economic return. Thus, the integrated nutrient and weed management practices in rice cultivation might be an effective way to achieve economic sustainability and efficient rice cultivation in eastern India. Shortages of farmyard manure and vermicompost could be supplemented by BSM and neem cake in the integrated module.